USE AND INFLUENCE OF DIGITAL SOCIAL NETWORKS IN THE LIFE OF UNIVERSITY STUDENTS IN REMOTE ACTIVITIES DURING PANDEMIC) - Silva, Meire Luci da [UNESP]; Santos, Guilherme Moreira dos [UNESP]; Almeida, Catia Candida; Silva, Nilson Rogerio da [UNESP] (Fundacao Univ Tocantins, 2022)
During the pandemic, the Internet and Digital Information and Communication Technologies were essential tools and resources for maintaining social interaction,work, health and teaching. However, its misuse can lead to negative impacts on physical and mental health. This article aimed to investigate the use and impact of Digital Social Networks in university students, in remote education, during the pandemic, as well as possible associations of these with sociodemographic and academic variables. Sample of 2034 university students from Brazilian higher education institutions. Developed and applied two semi-structured questionnaires related to the characterization of sociodemographic, academic and quarantine data and, another on the use of Digital Social Networks Data analysis by descriptive and inferential statistics. There was ambiguity of the positive and negative use of sociais networks. Identified a positive relationship in view of the possibility of continuity of social and academic life, as a source of leisure and information. The negative relationship was identified considering the health impairments with impact on sleep and mental health. Identification by the participants that abusive use is addictive and dangerous.
Keywords: Social Networking; Students; Education; Distance; Student Health; Covid-19